Validation of the new COPD assessment test translated into Thai in patients with chronic obstructive pulmonary disease - Pothirat,C. (BioMed Central, 2015)
© Pothirat et al. Background: The COPD Assessment Test (CAT™) is a new questionnaire that has been developed recently for measuring the COPD patient's health status. It is known to have a good correlation with disease specific health status measured by St. George's Respiratory Questionnaire (SGRQ). For the wider application in clinical practice, it has been validated in many countries. We evaluated the reliability and validity of the translated CAT questionnaire for Thai COPD patients. Methods: The study was designed as a cross-sectional validation study enrolling stable Thai COPD patients from three academic centers in Thailand at a single visit. The original CAT questionnaire was translated to Thai through linguistic validation process. The official Thai CAT and SGRQ questionnaires were filled by Thai patients after orientation by the out-patient nurse. The reliability of all items was assessed by Cronbach's formula for coefficient using pooled data from all patients. The validity of the questionnaire was tested using Pearson's correlation with SGRQ. Results: A total of 98 Thai COPD patients completed the official Thai CAT questionnaire; 83% were male, mean age 71 years (SD 8.2), and % predicted of FEV1 56.6% (SD 20.9). The official Thai CAT questionnaire was shown to have a high internal consistency (Cronbach's α coefficient = 0.853). The assessment of validity of official Thai CAT questionnaire was moderately correlated with that of SGRQ (r = 0.652). Conclusions: The official Thai CAT questionnaire has an acceptable reliability and validity. It can be expected to serve as a short and simple tool for assessment of the health status of Thai COPD patients.